EFEKTIVITAS PERAN GURU PAI DALAM PEMBINAAN AKHLAK SISWA MELALUI PENGUATAN PENDIDIKAN AGAMA DAN BUDAYA RELIGIUS - Ma'fiyah Ma'fiyah; Endah Mawarny; Yunus Yunus (STKIP Pesisir Selatan, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers at Malangke State Junior High School in fostering students' morals, the efforts made, the obstacles faced, and solutions to improve the effectiveness of learning. This study is a qualitative study. In collecting data through in-depth interviews conducted by question and answer while face to face with informants, namely 1 principal, 5 teachers, 10 students, 3 parents and 3 alumni. The results of the study indicate that the role of PAI teachers at Malangke State Junior High School focuses on strengthening religious education through providing information and resources related to morals, as well as assignments that train students' responsibility. Efforts to foster morals carried out by PAI teachers include cultivating religious culture, such as shaking hands when going home from school, greeting teachers, and guiding vehicles when entering the school gate. In addition, teachers make it a habit to give alms every Friday to foster an attitude of generosity, caring, and sincerity. The obstacles faced include limited provision of learning materials that do not cover all students and less supportive learning situations. The solutions implemented by Islamic Religious Education teachers to improve learning effectiveness include addressing these obstacles, for example, by providing material notes to students who do not yet have textbooks or worksheets.